Acute human self-poisoning with imidacloprid compound: a neonicotinoid insecticide. - Fahim Mohamed; Indika Gawarammana; Thomas A Robertson; Michael S Roberts; Chathura Palangasinghe; Shukry Zawahir; Shaluka Jayamanne; Jaganathan Kandasamy; Michael Eddleston; Nick A Buckley; Andrew H Dawson; Darren M Roberts (PLoS ONE)
Background Deliberate self-poisoning with older pesticides such as organophosphorus compounds are commonly fatal and a serious public health problem in the developing world. The clinical consequences of self-poisoning with newer pesticides are not well described. Such information may help to improve clinical management and inform pesticide regulators of their relative toxicity. This study reports the clinical outcomes and toxicokinetics of the neonicotinoid insecticide imidacloprid following acute self-poisoning in humans. Methodology/principal findings Demographic and clinical data were prospectively recorded in patients with imidacloprid exposure in three hospitals in Sri Lanka. Blood samples were collected when possible for quantification of imidacloprid concentration. There were 68 patients (61 self-ingestions and 7 dermal exposures) with exposure to imidacloprid. Of the self-poisoning patients, the median time to presentation was 4 hours (IQR 2.3-6.0) and median amount ingested was 15 mL (IQR 10-50 mL). Most patients only developed mild symptoms such as nausea, vomiting, headache and diarrhoea. One patient developed respiratory failure needing mechanical ventilation while another was admitted to intensive care due to prolonged sedation. There were no deaths. Median admission imidacloprid concentration was 10.58 ng/L; IQR: 3.84-15.58 ng/L, Range: 0.02-51.25 ng/L. Changes in the concentration of imidacloprid in serial blood samples were consistent with prolonged absorption and/or saturable elimination. Conclusions Imidacloprid generally demonstrates low human lethality even in large ingestions. Respiratory failure and reduced level of consciousness were the most serious complications, but these were uncommon. Substitution of imidacloprid for organophosphorus compounds in areas where the incidence of self-poisoning is high may help reduce deaths from self-poisoning.